(untitled) (Journal of Informatics Education and Research, 2025)
The growing integration of artificial intelligence (AI) in higher education is transforming the way students interact with both their academic work and personal lives. AI has a significant impact on various aspects of students’ well-being, including their mental health, social connections, and educational experiences. During this discussion, the present research work also offers advantages, such as personalised learning, mental health support, and more efficient communication, while also presenting challenges, including digital exhaustion, social isolation, technology-related stress, and a decline in human interaction. AI technologies, particularly those based on natural language processing (NLP) and machine learning (ML), are becoming increasingly scalable and accessible tools for supporting both psychological well-being and academic performance in higher education. This research paper will help ushelp us understand that that AI-driven tools offer continuous 24/7 support, overcoming barriers of time and distance, unlike traditional therapy methods, which are often limited by factors such as location, cost, and availability. The review also discusses that as AI becomes increasingly integrated into education, it becomes essential to create strategies that minimise its adverse impacts while fostering the overall well-being of students. A sample of 297 individuals was collected to obtain the study’s results. The factors exploring the “Impact of Artificial Intelligence on Psychological Well-Being and Academic Performance of Students in Higher Education” are Digital Literacy and technical competence, Personalised and adaptive learning, Immediate feedback and support and Academic assistance and accessibility.